Family social capital and entrepreneurship in rural China: potential mediating mechanisms - Jiafeng Gu (Economic Change and Restructuring, 2024)
Promoting rural family entrepreneurship is an effective way to realize rural revitalization. The primary aim of this study is to assess the entrepreneurial impact of family social capital on rural households in China. The objective of this study is to understand how family social capital affects rural entrepreneurship in a Chinese context. Using data from the 2020 China Family Panel Studies, this study empirically tests the effect of family social capital on rural family entrepreneurship. Research shows that family social capital is significantly and positively correlated with rural family entrepreneurship, indicating that it is an essential determinant in promoting rural family entrepreneurship. Internet use is an effective transmission path for family social capital, which affects rural entrepreneurship, and the impact of rural entrepreneurship varies with family size and household head characteristics. This study not only enriches the theoretical understanding of rural entrepreneurship but also sheds light on the behavioral mechanisms that explain the entrepreneurial process of rural households. To promote rural entrepreneurship and revitalization, it is important to be adept at activating family social capital.